2021
DOI: 10.3389/feart.2021.596860
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radiation Prediction Using Different Machine Learning Algorithms and Implications for Extreme Climate Events

Abstract: Solar radiation is the Earth’s primary source of energy and has an important role in the surface radiation balance, hydrological cycles, vegetation photosynthesis, and weather and climate extremes. The accurate prediction of solar radiation is therefore very important in both the solar industry and climate research. We constructed 12 machine learning models to predict and compare daily and monthly values of solar radiation and a stacking model using the best of these algorithms were developed to predict solar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 81 publications
0
30
0
1
Order By: Relevance
“…Shahab et al, (2021) discussed the application of different types of deep learning algorithms in the field of solar and wind energy resources and evaluated their performance with a new taxonomy [59]. Huang et al, (2021) considered the superposition and XGBoost models and concluded that they are the best models for predicting solar radiation [60]. These are the latest technologies in the renewable energy industry.…”
Section: Discussionmentioning
confidence: 99%
“…Shahab et al, (2021) discussed the application of different types of deep learning algorithms in the field of solar and wind energy resources and evaluated their performance with a new taxonomy [59]. Huang et al, (2021) considered the superposition and XGBoost models and concluded that they are the best models for predicting solar radiation [60]. These are the latest technologies in the renewable energy industry.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, the binary precipitation is predicted using the multinomial regression version (i.e., the elastic net logistic regression) of our model. While new machine learning techniques like the classification and regression tree (CART) can have better model skill in multi-class prediction of climate variables (Choubin et al, 2018;Huang et al, 2021), the elastic net logistic regression is tested to demonstrate flexibility and consistency with altered deviance functions. The multinomial regression may have more use in practical application since amplitudes of the predictand tend to be underestimated because of the regularization (Peng et al, 2020).…”
Section: An Alternative Multinomial Regression Modelmentioning
confidence: 99%
“…That function can be used in a different dataset, named testing one, to evaluate the model, and if the results are satisfactory, it can be used in the classification or regression of any kind of application needed. In that group we find methods, such as Decision Trees, e.g., Random Forest (RF) [5] or XGBoost (XGB) [6], Artificial Neural Networks (ANN) [7], Deep Learning (DL) [8], and Support Vector Machine (SVM) [9]. The second group in machine learning is unsupervised learning (Figure 1), in which algorithms do not have labelled data to train from, and must decide upon other ways to divide a given dataset, or reduce the dimensions of it, for further analysis.…”
Section: Introductionmentioning
confidence: 99%